Rescuing Suboptimal Outcomes of Subthalamic Deep Brain Stimulation in Parkinson Disease by Surgical Lead Revision. Issue 2 (6th March 2019) - Nickl, Robert C; Reich, Martin M; Pozzi, Nicoló Gabriele; Fricke, Patrick; Lange, Florian; Roothans, Jonas; Volkmann, Jens; Matthies, Cordula
Abstract: BACKGROUND: Clinical trials have established subthalamic deep-brain-stimulation (STN-DBS) as a highly effective treatment for motor symptoms of Parkinson disease (PD), but in clinical practice outcomes are variable. Experienced centers are confronted with an increasing number of patients with partially "failed" STN-DBS, in whom motor benefit doesn't meet expectations. These patients require a complex multidisciplinary and standardized workup to identify the likely cause. OBJECTIVE: To describe outcomes in a series of PD patients undergoing lead revision for suboptimal motor benefit after STN-DBS surgery and characterize selection criteria for surgical revision. METHODS: We investigated 9 PD patients with STN-DBS, who had unsatisfactory outcomes despite intensive neurological management. Surgical revision was considered if the ratio of DBS vs levodopa-induced improvement of UPDRS-III (DBS-rr) was below 75% and the electrodes were found outside the dorsolateral STN. RESULTS: Fifteen electrodes were replaced via stereotactic revision surgery into the dorsolateral STN without any adverse effects. Median displacement distance was 4.1 mm (range 1.6-8.42 mm). Motor symptoms significantly improved (38.2 ± 6.6 to 15.5 ± 7.9 points, P  < .001); DBS-rr increased from 64% to 190%. CONCLUSION: Patients with persistent OFFmotor symptoms after STN-DBS should be screened for levodopa-responsiveness, which can serve as a benchmark for best achievable motor benefit. Even small horizontal deviations of the lead from the optimal position within the dorsolateral STN can cause stimulation responses, which are markedly inferior to the levodopa response. Patients with an image confirmed lead displacement and preserved levodopa response are candidates for lead revision and can expect significant motor improvement from appropriate lead replacement.